2004
DOI: 10.2298/hemind0412569j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic models of reaction systems for the in situ epoxidation of unsaturated fatty acid esters and triglycerides

Abstract: Mathematical models that describe the kinetics of reaction systems for the in situ epoxidation of unsaturated fatty acid esters or triglycérides with organic peracids are reviewed in this paper. The advantages and inadequacies of each model are discussed. A mono-phase pseudo-first order kinetic model was compared with a two phase model based on the Langmuir-Hinshelwood-Hougen-Watson (LHHW) postulates proposed by the authors of this paper. The comparison was performed on the experimentally determined values for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 11 publications
0
30
0
Order By: Relevance
“…[13] In the presence of a heterogeneous solid catalyst, the peroxyacid formation step includes different substeps, such as diffusion of reactants into catalyst pores, adsorption of reactants on the catalyst surface, reaction at the catalyst surface, and diffusion of products from the catalyst to the bulk reaction mixture. The in situ epoxidation of cottonseed oil with PAA in the presence of a heterogeneous acid catalyst can be depicted as follows: All the experiments were carried out isothermally, under a stirring speed of 2400 rev/min, to ensure that there is no diffusional mass transfer resistance at the solid-liquid and liquid-liquid interfaces, and also it has been proved that the intraparticle diffusional effect is negligible.…”
Section: Epoxidation Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] In the presence of a heterogeneous solid catalyst, the peroxyacid formation step includes different substeps, such as diffusion of reactants into catalyst pores, adsorption of reactants on the catalyst surface, reaction at the catalyst surface, and diffusion of products from the catalyst to the bulk reaction mixture. The in situ epoxidation of cottonseed oil with PAA in the presence of a heterogeneous acid catalyst can be depicted as follows: All the experiments were carried out isothermally, under a stirring speed of 2400 rev/min, to ensure that there is no diffusional mass transfer resistance at the solid-liquid and liquid-liquid interfaces, and also it has been proved that the intraparticle diffusional effect is negligible.…”
Section: Epoxidation Kineticsmentioning
confidence: 99%
“…The model was developed based on the assumptions made by Janković and Sinadinović-Fišer, [13] and the model that fits the experimental data was based on a chemisorption mechanism as shown below. Besides the reaction of PAA formation (Reaction 5), the derived model includes the epoxidation reaction (Reaction 6) and the reactions involving oxirane cleavage (Reactions 7a and 7b).…”
Section: Epoxidation Kineticsmentioning
confidence: 99%
“…The mechanism for the in situ epoxidation in the presence of homogeneous catalyst is generally described as follows: (i) formation of peroxyacetic acid in the aqueous phase in the presence of catalyst; (ii) transfer of peroxyacetic acid from the aqueous phase to the oil phase; (iii) reaction of peroxyacetic acid in the oil phase to produce epoxides and to release acetic acid; (iv) degradation of the epoxide ring in the oil phase, as well as at the oilaqueous interface; (v) transfer of acetic acid from the oil phase back to the aqueous phase [20].…”
Section: Kinetic Modelmentioning
confidence: 99%
“…Janković and Sinadinović-Fišer [76] have already postulated a kinetic model for the in situ formation of peracetic acid from acetic acid and hydrogen peroxide in the presence of a homogeneous acid catalyst. The mechanism can be summarized in the following steps: (i) formation of peracetic acid in the presence of the catalyst and (ii) reaction between peracetic acid and the double bonds to produce oxirane rings, releasing acetic acid.…”
Section: Kinetic Model For the In Situ Epoxidation Of Grape Seed Oilmentioning
confidence: 99%
“…There is a small diference among these values and our determined one (7.3 kcal/mol). Janković and Sinadinović-Fišer [76] concluded that the number and the position of the double bonds, their position with respect to the carboxylic group, and the presence of cis-or trans-isomers have …”
Section: Kinetic Model For the In Situ Epoxidation Of Grape Seed Oilmentioning
confidence: 99%